OPTIMIZATION OF MACHINERY FIXTURE DESIGN THE MAIN COMPONENTS OF SLING BEARINGS USE A PNEUMATIC SYSTEM - fuzi rachmat ramdhan; Faiz Azri; Ghany Heryana; Dianta Mustofa Kamal; Fuad Zainuri; Hady Sofyan (Sekolah Tinggi Teknologi Wastukancana, 2023)
Sling bearings are one of the important components in the cable car transportation system. These bearings function to support the weight of the cable car and reduce friction between the train and the rail/sling so that the train can move smoothly and safely. To produce quality sling bearings, a precise and accurate machining process is required. The manufacturing process of ropeway sling bearings goes through a machining process, where raw materials that are usually metals or metal alloys will be cut, shaped, and polished to form the desired bearing shape. Fixture machining is one of the most commonly used techniques in the machining process, where the workpiece is clamped or fastened to a specially designed fixture so that the workpiece remains stable during the machining process. The purpose of this engineering is to produce a fixture design for sling bearing components with increased quantity and quality of products on CNC machines by validating the design through simulation. In this study, tests were conducted using a conventional machining fixture and a machining fixture equipped with a pneumatic system. The test results show that the machining fixture equipped with a pneumatic system is able to increase the production speed and efficiency of cable car sling bearings by up to 20% compared to the conventional fixture. This research makes an important contribution to the cable car sling bearing manufacturing industry in improving production efficiency and final product quality. In addition, this research can also be a reference for further research on the optimization of the cable car sling bearing production process.